(w-7)(3w+7)=0

Simple and best practice solution for (w-7)(3w+7)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (w-7)(3w+7)=0 equation:


Simplifying
(w + -7)(3w + 7) = 0

Reorder the terms:
(-7 + w)(3w + 7) = 0

Reorder the terms:
(-7 + w)(7 + 3w) = 0

Multiply (-7 + w) * (7 + 3w)
(-7(7 + 3w) + w(7 + 3w)) = 0
((7 * -7 + 3w * -7) + w(7 + 3w)) = 0
((-49 + -21w) + w(7 + 3w)) = 0
(-49 + -21w + (7 * w + 3w * w)) = 0
(-49 + -21w + (7w + 3w2)) = 0

Combine like terms: -21w + 7w = -14w
(-49 + -14w + 3w2) = 0

Solving
-49 + -14w + 3w2 = 0

Solving for variable 'w'.

Factor a trinomial.
(-7 + -3w)(7 + -1w) = 0

Subproblem 1

Set the factor '(-7 + -3w)' equal to zero and attempt to solve: Simplifying -7 + -3w = 0 Solving -7 + -3w = 0 Move all terms containing w to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -3w = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -3w = 0 + 7 -3w = 0 + 7 Combine like terms: 0 + 7 = 7 -3w = 7 Divide each side by '-3'. w = -2.333333333 Simplifying w = -2.333333333

Subproblem 2

Set the factor '(7 + -1w)' equal to zero and attempt to solve: Simplifying 7 + -1w = 0 Solving 7 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -1w = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -1w = 0 + -7 -1w = 0 + -7 Combine like terms: 0 + -7 = -7 -1w = -7 Divide each side by '-1'. w = 7 Simplifying w = 7

Solution

w = {-2.333333333, 7}

See similar equations:

| 3*0-6y=12 | | 5(x+4)-2(x-3)= | | p-5/4=3 | | t/5-6=7 | | 31n(x+6)=9 | | (a-4)(5a+3)(a+4)= | | 12=160-12t-16t^2 | | 80,000.00+209.00x=599.00x. | | x/5=9/6 | | (24000-x)*(17600/x)=1600 | | 80,000.00+209.00=599.00x. | | cos((7π)/4)= | | (x-2)*(x+7)=0 | | (4x-7)(x^2-2x+1)= | | 7-16=8y-7y+3 | | (8a^-6)^(-2/3) | | (2x-7)(x+4y)= | | 4.5=4.5z-4.25+6.25+6.25 | | 80,000.00+209.00x=249,783.00 | | 7x-3(-5x-2)=-38 | | 80,000.00+209.00x=150,015 | | log[3](81)=3x+8 | | 6(y-3)-2=-4(4y+1)-4y | | 80,00000+209.00x=150,015 | | -2x((x^2)-25)(x-5)= | | 2*xln*x-x=0 | | -2x((x^2)-25)*(x-5)= | | 9[5-7(x-1)]+6[(3x+2)-5]=12x-341 | | -15.5=u/7 | | 7t^2(t-t^2+7t^3)= | | 9x+18-x=34 | | 7x+15x-2x=15-10 |

Equations solver categories